Neumann Problem of Quasilinear Elliptic Equations with Limit Nonlinearity in Boundary Condition (Journal of Partial Differential Equations, 2001)
This paper is concerned with the existence of solutions to the equation D_j(a^{ij}(x,u)D_i,u)-\frac{1}{2}D_sa^{ij}(x,u)D_iuD_ju + λ u = 0 on a bounded domain under the Neumann boundary condition aij(x,u)D_iuϒ_j = lul^{\frac{2}{n-2}}u.
Keywords: Neumann problem; quasilinear elliptic equation